2013
DOI: 10.1017/s0007114513000937
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strawberries increase the proliferative response of CD3/CD28-activated CD8+ T cells and the production of TNF-α in lipopolysaccharide-stimulated monocytes from obese human subjects

Abstract: Obesity increases the risk of developing bacterial and viral infections compared with normal weight. In a 7-week double-blind, randomised, cross-over trial, twenty obese volunteers (BMI between 30 and 40 kg/m 2 ) were fed freeze-dried strawberry powder or strawberryflavoured placebo preparations to determine the effects of dietary strawberries on immune function. Blood was collected at six time points during the study and peripheral blood mononuclear cells (PBMC) were isolated at each time point and activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
2
9
0
1
Order By: Relevance
“…Similar trend was seen after intake of freeze-dried strawberries [40,41], which also increased immunological response in obese subjects [42].…”
Section: Impact On Obesity Diabetes and Metabolic Syndromesupporting
confidence: 69%
“…Similar trend was seen after intake of freeze-dried strawberries [40,41], which also increased immunological response in obese subjects [42].…”
Section: Impact On Obesity Diabetes and Metabolic Syndromesupporting
confidence: 69%
“…We have recently reported that dietary strawberries induce beneficial changes in blood lipid profiles and sensitise ex vivo -derived monocytes in response to an immunological stimulant ( 21 , 22 ) . In the present study, we expanded our analyses to another fruit to further define the potential benefits of consuming different fruits in the obese population.…”
mentioning
confidence: 99%
“…In a separate intervention study, we observed an increase in the production of the pro-inflammatory cytokine TNF- in LPSstimulated monocytes from obese subjects after consuming strawberry powder [32]. In the study with strawberry powder, the subjects were given all of their meals for the duration of the study, which substantially reduced the likelihood that changes in dietary patterns influenced the production of TNF- in the monocyte population [32]. In the study with grape powder, we utilized dietary recall data in order to eliminate the possibility that diet was responsible for mediating the increased sensitivity of the monocyte population to LPS.…”
Section: Discussionmentioning
confidence: 83%
“…Previously, we determined that consumption of grape powder increased the production of two pro-inflammatory cytokines IL-1 and IL-6 by monocytes from obese subjects after ex vivo-stimulation with the bacterial component LPS [22]. In a separate intervention study, we observed an increase in the production of the pro-inflammatory cytokine TNF- in LPSstimulated monocytes from obese subjects after consuming strawberry powder [32]. In the study with strawberry powder, the subjects were given all of their meals for the duration of the study, which substantially reduced the likelihood that changes in dietary patterns influenced the production of TNF- in the monocyte population [32].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation